1990
DOI: 10.1007/bf01967824
|View full text |Cite
|
Sign up to set email alerts
|

Stability of somatostatin in total parenteral nutrition

Abstract: The stability of somatostatin, added to a total parenteral nutrition formula, in glass containers and in plastic ethylene vinyl acetate containers was investigated. The somatostatin concentration decreased immediately from 3 micrograms/ml to 0.3-0.6 micrograms/ml after addition to the emulsion. In spite of this rapid decrease, somatostatin concentrations remained stable with values of 0.4-0.7 micrograms/ml during the follow-up period (24 h). These findings could be explained assuming adsorption to the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Secondly, somatostatin has a very short biological half-life; a study in rats showed rapid disappearance of somatostatin from circulation ( t 1/2 = 1 min), followed by slow clearance from skin and muscle [ 19 ]. At the same time, in humans, it is about t 1/2 = 2–3 min [ 20 ]. It has been proposed that proteases are responsible for the rapid degradation of this hormone through catabolism [ 19 ].…”
Section: Characteristics Of Cs In Animalsmentioning
confidence: 99%
“…Secondly, somatostatin has a very short biological half-life; a study in rats showed rapid disappearance of somatostatin from circulation ( t 1/2 = 1 min), followed by slow clearance from skin and muscle [ 19 ]. At the same time, in humans, it is about t 1/2 = 2–3 min [ 20 ]. It has been proposed that proteases are responsible for the rapid degradation of this hormone through catabolism [ 19 ].…”
Section: Characteristics Of Cs In Animalsmentioning
confidence: 99%
“…Analogs of this drug have been investigated before, [11][12][13] but, to our knowledge, no stability studies have been performed with the parent molecule somatostatin, except for one publication reporting the loss of peptide in solutions for total parenteral nutrition. [14] Systematic investigations are, therefore, needed in order to gain more information on factors influencing the stability of this particular drug and of peptides in general. These data are essential for rational dosage form development, the design of stability studies, and shelf-life predictions, and they should result in a facilitated and accelerated development of suitable formulations, a prerequisite to obtain the desired pharmacological effect.…”
Section: Introductionmentioning
confidence: 99%